Effect of Secondary School Types to The School-Work Transition in Indonesia - Ruth Eviana Hutabarat; Brillian Akbar Aminullah; M. Afif Khoiruddin; Kartika Sari (Universitas Negeri Semarang, 2023)
The purpose of this study is to examine how the choice of the type of secondary school (JHS-SHS) affects transition decisions after graduating from high school. Using the multinomial logistic regression method, this study uses data from the Indonesian Family Life Survey (IFLS) wave five (2014) with a total of 3209 samples from all over Indonesia. The results showed that individual graduates from private schools had a positive toward the tendency to work informally. Private and public high school graduates tend not to work formally, respectively. Male individuals will tend to work informally and formal. In contrast, female individuals tend to continue their higher education. Individuals with married status tend to work informal, and unmarried individuals tend to continue their higher education. Individuals with a female head of home care to work in the formal sector and those with a male head of home tend to continue their higher education. while individuals who live outside Java/Bali tend to work in the informal sector.